A study of samurai income and entrepreneurship : - Yamamura, Kozo (Harvard University Press, 1974)
Introduction; The background of the Bannerman; The Bannerman's "Increasing Poverty"; Social and Economic Mobility of the Bannerman; Demographic Characteristics of the Bannerman; The Houseman and the Daimyo Retainer; The Samurai Role in Banking and Modern Industry; Conclision...